Odpowiedź :
Odpowiedź:
8+7= 15
-8 +7 = -1
8 +(-7)= 8-7= 1
-8-7= - 15
4*5/8 ( skracamy 4 i 8 przez 4)= 5/2 = 2 i 1/2
16*3/8 ( skracamy 16 i 8 przez 8)= 2*3= 6
6/15 : 2/3= 6/15 *3/2( skracamy 6 i 2 przez 2, oraz 15 i 3 przez 3)= 3/5
7/9 : 7/3= 7/9 *3/7( skracamy 3 i 9 przez 3, oraz 7 i 7 przez 7)= 1/3
Szczegółowe wyjaśnienie:
Odpowiedź:
8+7= 15
-8+7=7-8= -1
8+(-7)=8-7=1
-8-7= -15
4* 5/8=2 * 5/4 = 10/4 = 5/2 = 2,5
16*3/8= 2 * 3/1 = 6/1 = 6
6/15:2/3= 6/15 * 3/2 = 3/15 * 3/1 = 3/5 * 1/1 = 3/5
7/9:7/3 = 7/9 * 3/7 = 1/9 * 3/1 = 1/3 * 1/1 = 1/3
Szczegółowe wyjaśnienie: